Chemical nature of PM2.5 and PM10 in Xi'an, China: Insights into primary emissions and secondary particle formation. (September 2018) - Dai, Qili; Bi, Xiaohui; Liu, Baoshuang; Li, Liwei; Ding, Jing; Song, Wenbin; Bi, Shiyang; Schulze, Benjamin C.; Song, Congbo; Wu, Jianhui; Zhang, Yufen; Feng, Yinchang; et al.
Abstract: In Xi'an, a city that frequently experiences serious PM pollution in northern China, 1476 PM10 and 1464 PM2.5 valid daily filter samples were collected at six sites from December 2014 to November 2015 and analyzed for 29 species. The annual mean PM10 and PM2.5 concentrations were 149.4 ± 93.1, 108.0 ± 70.9 μg/m 3, respectively. Organic carbon (OC) is the predominant PM2.5 component while crustal material predominated in PM10 . Sulfate concentrations, which was the largest component in Xi'an PM in previous studies, were lower than nitrate. Winter sulfate, OC, and elemental carbon (EC) have decreased since 2003, while nitrate remained constant in recent years and the ratio of NO3 − /SO4 2− increased from 0.4 in 2006 to 1.3 in 2014. This result suggests that the motor vehicle contribution to PM has increased relative to coal-fired power plant emissions over the past decade. The mass fractions of crustal material, sulfate, and EC in PM2.5 decreased as the PM2.5 concentrations increased from "clean" days (<50 μg/m 3 ) to the highest values, while nitrate significantly increased. Despite forming through secondary reactions, the high concentrations of SOC and SO4 2− in winter are attributed to primary emissions and particularly to residential heating and cooking with coal. Primary SOC and SO4 2− accounted for 33% and 42% of their total PM2.5 concentrations in winter, respectively. Therefore, control measures applied to these primary sources can substantially improve air quality. Graphical abstract: Image 1 Highlights: 33% and 42% of ambient SOC and sulfate in winter were from primary emissions. Sulfate, OC, and EC have decreased during wintertime since 2003. The ratio of NO3 - /SO4 2- increased from 0.4 in 2006 to 1.3 in 2014. Abstract : The particulate species that are normally considered to be secondary are actually primary.